Exploring Secondary Students' Perceptions of ELENA (English Letter and Announcement) Learning Media in Enhancing Writing Skill - Ma'arif, Iin Baroroh; Rohmah, Charisa Nur (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2025)
This study investigates students’ perceptions of the use of ELENA learning media in enhancing their writing skills. Employing a qualitative research design, data were collected through semi-structured interviews, classroom observations, and questionnaires to capture in-depth insights into students’ experiences. The combination of these methods allowed for a comprehensive understanding of students’ experiences and attitudes toward the integration of ELENA in the learning process. The findings reveal that 92 % students responded positively to the integration of ELENA into the learning process. They perceived the media as engaging, supportive, and effective in improving their motivation, organization of ideas, and overall writing performance. Moreover, the interactive and user-friendly design of ELENA was perceived as beneficial in making writing practice more enjoyable and accessible. These results suggest that ELENA has strong potential as an innovative instructional tool for improving students’ writing competence while simultaneously fostering greater interest and participation in classroom activities.